Improving Students’ Speaking Skill Through Role Play Technique of a Vocational High School in Sungai Penuh - Septiawan, Wawan (Langue (Journal of Language and Education), 2024)
In international relations, English language skills are very important to be able to participate in the wider world of work. Speaking skills are measured by the ability to carry out conversations in the language. This fact makes teachers think that speaking skills must be mastered by their students. This research was designed in classroom action research. This aimed to improve students' speaking skills among vocational school students in Sungai Penuh. A total of twenty-eight (28) participants were involved and carried out through two cycles. Each cycle consists of three meetings. The first and second meetings of each cycle were used to implement role-play techniques. Meanwhile, the last meeting of each cycle is for the speaking test. During this research, the researcher was assisted by a collaborator. Collaborator is a teacher who teaches English at a vocational school in Sungai Banyak. The instruments of this research are questionnaires and speaking tests. The results of this study showed that students' speaking skills improved significantly. This is proven by the average student scores. In cycle I, student achievement was 70.14, cycle II 82.28. Before researchers conducted this research, the average student score was 60.78. These results indicate that role playing techniques can improve students' speaking skills. Improving students' speaking skills is influenced by several factors. Namely: components of effective learning, classroom management and student awareness themselves.